Barriers to innovation and knowledge generation: The challenges of conducting business and social research in an emerging country context - James C. Ryan; Timothy M. Daly (Journal of Innovation & Knowledge (JIK), 2019)
The Middle East, as a region, contributes proportionally less to new knowledge generation than other parts of the world. The United Arab Emirates (UAE) has sought to correct this imbalance through efforts to promote a knowledge-based economy and through educational investment. In light of these advances, significant challenges still remain in the promotion and production of high quality research in the social sciences, including business. The current monograph highlights the vital importance of such research to the social and economic development of the UAE. Reflecting on nearly a decade of conducting research in the UAE with varying degrees of success the authors highlight critical incidents, experiences and observations which serve to illustrate the challenges of new knowledge creation in the business and social sciences. Discussions focus on identifiable barriers to high quality research at both the micro and macro levels, within and outside the UAE, with specific recommendations on how such barriers can be overcome.
Keywords: J00; O10; O20; O30; Z10; 650; Research challenges; Middle East; Diseases of academic research